Limited representation of drinking-water contaminants in pregnancy–birth cohorts - Makris, Konstantinos C.; Andra, Syam S. (My University, 2014)
Water contamination and noise have been consistently the least assessed environmental/lifestyle exposures in pregnancy–birth cohorts (PBC). Water quality surveillance data collected during the past decade within urban drinking-water distribution systems call for re-evaluation of water and health issues in the developed world. The objectives of this scientific commentary were to (i) highlight the extent of appraisal of water contamination in exposure assessment studies of PBC, worldwide, and (ii) propose recommendations to increase awareness of emerging water-related risks through their improved representation into PBC study designs in urban centers. Three scientific literature databases (Scopus, PubMed, and Web of Science) were used for a systematic search on worldwide PBC and their publications that considered water contamination and health outcomes. Publicly-available e-databases (ENRIECO, BIRTHCOHORTS, and CHICOS) were also employed for detailed exploration of existing European Union (EU)-based PBC. Out of the 76 PBC identified in the EU territory, only 12 of them incorporated water contamination into their study designs. Among which only 6 PBC published scientific articles that either included data on water contamination and/or water intake estimates. Trihalomethanes but not other disinfection by-products were mostly studied in the PBC around the globe, while fluoride, atrazine, perfluorinated compounds, tetrachloroethylene, and lead were studied to a lesser extent as water contaminants. It appears that chemical-based water contamination and corresponding human exposures represent a largely underappreciated niche of exposure science pertaining to pregnant mother and children's health in PBC. Future PBC studies should grasp this opportunity to substantially reform elements of water contamination in their exposure assessment protocols and effectively combine them with their epidemiological study designs.
Keywords: Chemical mixtures; Disinfection byproducts; Endocrine disrupting chemicals; Environmental co-exposures; Pregnancy-birth cohort; Water and health